Outcome and survival analysis of pulmonary metastasectomy for primary sarcoma with pulmonary metastases - Chang, Chih-Hsiang; Chiang, Xu-Heng; Lin, Mong-Wei; Kuo, Shuenn-Wen; Huang, Pei-Ming; Hsu, Hsao-Hsun; Chen, Jin-Shing (Frontiers in Surgery, 2024)
BackgroundSarcomas are rare malignancies, accounting for approximately 1% of all cancers. Pulmonary metastases are the most preferential site for distant metastasis in malignant soft tissue sarcomas. Despite the lack of evidence from large randomized trials to support treatment guidelines, surgical resection of resectable metastatic tumors remains the current standard of care. This study aimed to explore the survival status of patients with soft tissue sarcoma after resection of pulmonary metastases.MethodsThis study is a retrospective analysis of patients who mestastasectomy by means of lobar or sublobar resections at National Taiwan University Hospital and its branches. The statistical and investigation period was from February 2007 to December 2020.ResultsAmong 110 samples during the investigation period, the overall 5-year survival rate was 62.9%, which was higher than the 15%–50.9% reported previously. A disease-free interval of more than 12 months and the occurrence of local recurrence of sarcoma at the time of resection of pulmonary metastases are associated with overall survival. Most of the samples were treated with minimally invasive surgery (VATS), and therefore, most patients had a shorter hospital stay and better postoperative recovery.ConclusionFor pulmonary metastatic sarcoma, pulmonary metastasectomy is a relatively safe treatment method with short hospital stay and short ICU stay. The results of this study suggest that VATS is preferred over thoracotomy, but further observations are needed to confirm these findings.